Pengaruh User Generated Content Terhadap Keputusan Pembelian Produk The Originote (Survei Pada Pelanggan Followers TikTok @theoriginote) - Mellyani, Astrid Puspita; Siregar, Salim (Universitas Indraprasta PGRI Jakarta, 2025)
This study was conducted looking at the current phenomenon, namely User Generated Content which influences purchasing decisions. This study was conducted with the aim of determining the influence of User Generated Content on purchasing decisions for The Origiinote products. Using a quantitative descriptive method by distributing questionnaires online to 100 respondents who are followers of the TikTok social media account @theoriginnote, then the data was processed using SPSS by conducting Validity and Reliability Tests, Classical Assumption Tests, and Simple Linear Regression Tests. So that the sig value of 0.000 was obtained, which means that there is a significant influence of User Generated Content on purchasing decisions. Based on the results of the determination coefficient of 87.6%, aspects of User Generated Content influence Purchasing Decisions and with 12.4% as other aspects outside the User Generated Content variable